Useful strategy in the design of energy-efficient buildings using innovative daylighting systems - Han, Hyun Joo (2010)
This research work has been carried out to utilize daylight more effectively for indoor illumination in an energy efficient building without any compromise on indoor environmental quality; especially the visual comfort on task plane. Two different daylighting systems have been designed and constructed, and a series of tests have been performed to assess their photometric characteristics as well as their performance. A typical system considered has an optic concentrator capable of tracking the sun and making high density fluxes of solar rays. It consists of either dish or funnel shaped concentrators followed by optical fiber cables and diffusers at the end. The design of a dish concentrator (diameter less than 30 cm) is prepared by rotating a simple parabolic profile in compliance with the major physical requirements. This geometrical simplicity has also been applied for the design of a funnel shaped concentrator created by combining two parabolas. When the sunlight is highly focused, it is then redirected and undergoes a number of reflections to enter a light guide for its final transmission to the terminal device. The light reaching the terminal device finally gets consumed by the interior of a building for indoor illumination.